Effectiveness of Vermicompost Priming in Improving the Physiological Quality of Soybean Seeds - Permatasari, Dewi Rahmawati Intan; Ilyas, Satriyas; Qadir, Abdul (Journal of Tropical Crop Science, 2025)
Soybean seeds deteriorate rapidly, especially under humid tropics. An effective method for boosting seed germination is invigoration, which is applied as a pre-planting seed treatment to stimulate the metabolic activity in the seed. The research aimed to compare the effectiveness of vermicompost priming with other invigoration methods in improving the physiological quality of soybean seeds. The experiment was arranged in a split-plot, randomized design. The main plots were seed lots based on low, medium, and high germination of three soybean varieties (“Argomulyo”, “Detap 1”, and “Devon 1”). Subplot, invigoration method: control, matriconditioning with rice husk charcoal, a ratio of seed (g): rice husk charcoal (g): water (mL) 9:6:7 for 12 hours; osmoconditioning with 15% PEG 6000 solution, a ratio of seed (g): solution (mL) was 1:2 for 12 hours, and vermicompost priming with a ratio of seed (g): vermicompost (g): water (mL) 12:14:12 for 18 hours. Each experimental unit used 120 g of seeds. The invigoration treatment was conducted in a room with a temperature of 25 ± 2°C and a relative humidity (RH) of 65-70%. The results showed that invigoration treatment can be used on soybean seeds with moderate viability (germination rate of 70-79%). In “Argomulyo” and “Detap 1”, the seed physiological quality increased with vermicompost priming, and in “Devon 1”, it increased with matriconditioning. The enhanced physiological quality of soybean seeds may be attributed to the complete nutrient and phytohormone content in vermicompost.